"EMPOWERING CHOICES: A COMPREHENSIVE ANALYSIS OF FAMILY PLANNING AWARENESS AND ATTITUDES AMONG ELIGIBLE COUPLES IN SVBP HOSPITAL, MEERUT" - Nadiya Gulzar; Nayeema Rafiq; Ulfat Farooq (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
ABSTRACT In this descriptive study, Meerut-based eligible couples' knowledge and attitudes about family planning methods are examined. 50 participants were chosen for the study using a purposive sampling technique, and they each received a structured questionnaire. Demographic information, awareness of family planning options, and opinions towards those options were all covered by the questionnaire. The study's conclusions offer insightful information on participants' knowledge of and attitudes about family planning practises. This study adds to our understanding of attitudes towards family planning within the specific healthcare context.